IN SILICO STUDIES AND CYTOTOXICITY ASSAY OF BENZYLIDENE BENZO HYDRAZIDE DERIVATIVES ON CANCER STEM CELL - GAURU, IMANUEL; ALAM, YUSUF S.; SANTOSO, MARDI; FADLAN, ARIF; AFFIFAH, NUR R.; N. ANDIFA, VINDA A.; PUDJIASTUTI, PRATIWI; MARTAK, FAHIMAH (International Journal of Applied Pharmaceutics, 2025)
Objective: This study aimed to evaluate the biological activity of benzylidene benzohydrazide derivatives against Cancer Stem Cells (CSCs) through in vitro cytotoxicity tests and silico analyses using molecular docking. Methods: Four hydrazone compounds, namely benzylidene benzo hydrazide (L1), 2-methyl benzylidene benzo hydrazide (L2), 2-nitro benzylidene benzo hydrazide (L3), and 2-bromobenzylidene benzo hydrazide (L4) were used for in silico and in vitro studies. The interaction between hydrazone compounds and the EGFR protein receptor (PDB ID: 1m17) was investigated using the AutoDock tools 1.5.7. The PASS server predicted the biological activities of hydrazone substances. ADMET of hydrazone compounds was assessed using the ADMETLab 2.0. Meanwhile, the cytotoxic activity test of hydrazone compounds on CSCs was evaluated using the MTT Assay method. Results: The results of molecular docking analysis of test compounds L1-L4 provide binding energy values ranging from -6.69 to-7.74 kcal/mol. The binding energy value of L1-L4 is lower than the reference Doxorubicin (-4.30 Kcal/mol). The results of the cytotoxicity test of test compounds with CSCs provide IC50 results for L1 of 0.220±0.360 μg/ml, L2 of 0.034±0.023 μg/ml, L3 of 0.355±0.276 μg/ml, L4 of 1.193±1.122 μg/ml and Doxorubicin of 0.220±0.180 μg/ml. These results indicate that hydrazone derivatives have the potential to be CSCs inhibitor. Conclusion: 2-methyl benzylidene benzo hydrazide (L2) had the potential as a CSCs inhibitor with vigorous cytotoxic activity in vitro against CSCs cell lines